??The Relative Importance of Predators for the Control of Nephotettix Spp. on Rice ? (Biological Sciences - PJSIR, 1995)
The rice green leafhoppers, Nephotettix spp. (Homoptera:Cicadellidae is one of the most devastating pests of ricethroughout the rice growing areas of Asia [1-4]. They act asan efficient vector of rice tungro virus, one of the most menacingdisease of rice [1].